Phytoadaptogen reverses the adverse effects of Naftussya bioactive water on dynamic muscle performance in healthy rats - Fihura, Oksana; Ruzhylo, Sofiya; Zakalyak, Nataliya (Quality in Sport, 2022)
Background.. Muscular performance is considered one of the attributes of health and non-specific resistance. Phytoadaptogens occupy an important place in the arsenal of means of increasing non-specific resistance and stress resistance. Many years of research of the Truskavetsian Scientific School of Balneology have demonstrated the adaptogenic properties of the main therapeutic factor of the resort, Naftussya bioactive water, as well as ozokerite and mineral baths. However, in contrast to the beneficial effect of the latter on stress resistance and the neuro-endocrine-immune complex, the effect on the physical performance is ambiguous. The purpose of this study is to test the ability of phytocomposition to prevent the adverse actotropic effect of Naftussya bioactive water at rats. Material and methods. The experimentt have been carried out at 42 female rats. Rats of the control group for 7 days loaded through a tube with tap daily water (2 mL once), while the animals of the other groups received according to a similar scheme daily water with the addition of 0,1 mL of Balm; bioactive Naftussya water per se or with the addition of 0,1 mL of Balm. The day after completion the course of water loads in the animal determined the urinary excretion of 17-ketosteroids, assessed the mineralocorticoid activity (MCA) by the urine K/Na ratio as well as the state of neutrophil phagocytosis by the number of absorbed latex particles. Results. It was found that the weekly use of Naftyssya bioactive water reduces the duration of swimming of rats to exhaustion by 30% compared to the daily water control. Addition of phytoadaptogen to Naftyssya softens its negative actotropic effect by up to -9%, and adding Balsam to daily water prolongs the maximum duration of swimming compared to the control by 11%. A positive correlation of the swimming test with 17-KS excretion and water diuresis was revealed, but a negative correlation with MCA, spontaneous diuresis and neutrophils phagocytosis. Conclusion. Phytoadaptogen reverses the adverse effects of Naftussya bioactive water on dynamic muscle performance in healthy rats by mitigating the decrease in the excretion of 17-ketosteroids and increased mineralocorticoid activity.